First person singular subject pronoun expression in Equatoguinean Spanish. - Padilla, Lillie (Journal of Monolingual & Bilingual Speech (JMBS), 2021)
The present study examines the linguistic and social factors that affect first person singular subject pronoun expression (SPE) in Equatoguinean Spanish. It also questions whether first person singular SPE in Equatoguinean Spanish supports or contradicts the tenets of the interface hypothesis. The data were analysed with the mixed effect software Rbrul. It consisted of transcriptions of audio recordings of 30 Equatoguinean participants in Malabo. The overt pronoun rate found in these data is 25.1%. The linguistic factors that also influence first person singular SPE are ambiguity, verb class and reference, whereas the social factors are education and speaker. Due to the low ranking of reference, the prediction of the interface hypothesis is supported in this study.